1972
DOI: 10.3181/00379727-139-36347
|View full text |Cite
|
Sign up to set email alerts
|

Pesticide Residues and Polychlorinated Biphenyl Levels in Diets, Urine, and Fecal Matter of Preadolescent Girls

Abstract: Description of six earlier Southern Region-al Studies with preadolescent girls 7 to 9 L., Poultry Sci. 41, 295 (1962). 20, 958 (1970.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

1975
1975
2008
2008

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 7 publications
1
6
0
Order By: Relevance
“…Low accumulation of BTs in Steller sea lion was also supported by the study of Evans et al [43], which indicated that more than 90% of BT intake was excreted through feces and urine. On the contrary, excreted organochlorine compounds were only 9 to 32% of the total intake in humans [44]. These observations, including the results of the present study, suggest that unlike organochlorines, BTs are largely excreted from the body of Steller sea lion and thus accumulated less in this animal.…”
Section: Biomagnification Of Bt In Steller Sea Lionsupporting
confidence: 41%
“…Low accumulation of BTs in Steller sea lion was also supported by the study of Evans et al [43], which indicated that more than 90% of BT intake was excreted through feces and urine. On the contrary, excreted organochlorine compounds were only 9 to 32% of the total intake in humans [44]. These observations, including the results of the present study, suggest that unlike organochlorines, BTs are largely excreted from the body of Steller sea lion and thus accumulated less in this animal.…”
Section: Biomagnification Of Bt In Steller Sea Lionsupporting
confidence: 41%
“…There are several reports of animal experiments with high level exposure to PCBs (Grant et al 1971, Hashimoto et al 1976, Hayes et al 1971), but only a few report any low-level exposure data. Price et al (1972) reported pesticide residues and PCB levels in diets, urine, and fecal matter of preadolescent girls. In their experiments, 88% of the ingested PCBs were not excreted and, presumably, they were retained in the body.…”
Section: Excretion Of Pcbsmentioning
confidence: 99%
“…The tentative acceptable daily intake in the U. S. has been set at 150 to 300 //g/day 102 , whereas the average intake has been calculated to be only 7 pg/day. 103 However, a study by Price et al 104 on the diet of 8 ' girls in Virginia found that while 4 had only traces of PCB (i.e., less than 0.001 ppm), 4 contained 200, 420, 580, and 840 jug/day. In certain areas, viz., northeast U. S., Japan, and much of Europe, persons eating considerable amounts of fish would be expected to exceed the FDA guidelines.…”
Section: F Levels Of Pcb's In Humans and Their Foodmentioning
confidence: 95%